Aloha :)
$$\sum\limits_{k=0}^nk2^k=\sum\limits_{k=1}^nk2^k=2\sum\limits_{k=1}^nk2^{k-1}=2\left.\sum\limits_{k=1}^nkx^{k-1}\right|_{x=2}=2\left.\sum\limits_{k=1}^n\frac{d}{dx}(x^k)\right|_{x=2}$$$$=2\frac{d}{dx}\left.\left(\sum\limits_{k=1}^nx^k\right)\right|_{x=2}=2\frac{d}{dx}\left.\left(\sum\limits_{k=0}^nx^k-1\right)\right|_{x=2}=2\frac{d}{dx}\left.\left(\frac{1-x^{n+1}}{1-x}-1\right)\right|_{x=2}$$$$=2\left.\frac{-(n+1)x^n\cdot(1-x)-(1-x^{n+1})\cdot(-1)}{(1-x)^2}\right|_{x=2}=2\left[(n+1)2^n+(1-2^{n+1})\right]$$$$=2\left[(n+1)2^n+1-2\cdot2^n\right]=2\left[(n-1)2^n+1\right]=(n-1)\cdot2^{n+1}+2$$